2001
DOI: 10.1002/jclp.1101
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment correlates of the therapeutic bond

Abstract: This study examined the association between pretreatment client characteristics and the therapeutic bond, which is defined as the emotional aspect of the therapeutic alliance. Three types of interpersonal problems and four indicators of emotional distress were measured and compared to the therapeutic bond and its subscales (role investment, empathic resonance, and mutual affirmation) measured early in treatment. Interpersonal problems related to being overly detached were associated with a poorer quality bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
(21 reference statements)
1
28
0
3
Order By: Relevance
“…Overall interpersonal distress, however, was associated with lower alliance quality. In a study of PD treatment of patients with a variety of clinical problems, Saunders (2001) found that interpersonal problems of a detached nature were negatively associated with specific aspects of the patient-rated alliance, including the affective bond, the patient's role investment in the therapy, as well as his or her sense of mutual affiliation with the therapist and ratings of therapist empathy.…”
Section: Interpersonal Problems As Predictors Of the Alliancementioning
confidence: 99%
“…Overall interpersonal distress, however, was associated with lower alliance quality. In a study of PD treatment of patients with a variety of clinical problems, Saunders (2001) found that interpersonal problems of a detached nature were negatively associated with specific aspects of the patient-rated alliance, including the affective bond, the patient's role investment in the therapy, as well as his or her sense of mutual affiliation with the therapist and ratings of therapist empathy.…”
Section: Interpersonal Problems As Predictors Of the Alliancementioning
confidence: 99%
“…Interpersonal problems also have been found to negatively impact outcomes for psychotherapy across therapeutic orientations (Borkovec, Newman, Pincus, & Lytle, 2002;Horowitz, Rosenberg, & Bartholomew, 1993;Markowitz et al, 1996). Furthermore, clients' difficulties in interpersonal functioning have a deleterious effect on the formation of the therapeutic alliance (Muran, Segal, Samstag, & Crawford, 1994;Paivio, 1998;Saunders, 2001). To the best of our knowledge, however, the relationship between problems in interpersonal functioning, therapeutic alliance, and outcome in psychotherapy remains unexamined.…”
mentioning
confidence: 96%
“…Ils ont voulu vérifier, entre autres, l'influence de quelques indicateurs de santé mentale sur la formation d'une alliance thérapeutique (Saunders, 2001). Ces études affichent une grande divergence dans leurs conclusions.…”
Section: Alliance Thérapeutique Et Santé Mentaleunclassified
“…Dans une étude réalisée auprès de 33 hommes souffrant d'anxiété, de dépression ou d'introversion sociale, Moras et Strupp (1982) ont démontré que les relations interpersonnelles sont reliées à la santé psychologique des clients, qui correspond à la somme des évaluations des cliniciens sur la sévérité des problèmes, l'intensité de la détresse subjective (somme des scores sur l'anxiété, la dépression et l'estime de soi) et la (Howgego et al, 2003;Saunders, 2001). En contrepartie, il ne semble pas y avoir de corrélation significative entre l'alliance thérapeutique et la symptomatologie des clients (Gaston et al, 1988;Saunders, 2001).…”
Section: éTudes Démontrant Un Lien Positif Entre L'alliance Thérapeutunclassified
See 1 more Smart Citation